Arachis virus Y, a new potyvirid from Brazilian forage peanut (Arachis pintoi) - Pantoja, Késsia Fátima Cunha [UNESP]; de Jesus Boari, Alessandra; Rossitto De Marchi, Bruno; Rezende, Jorge Alberto Marques; Kitajima, Elliot Watanabe; Gonçalves, Rivadalve Coelho; Assis, Giselle Mariano Lessa; Blawid, Rosana; Krause-Sakate, Renate [UNESP] (Springer Nature, 2020)
The complete nucleotide sequence of a new member of the family Potyviridae, which we propose to name “Arachis virus Y” (ArVY), is reported from forage peanut plants (Arachis pintoi) exhibiting virus-like symptoms. The ArVY positive-sense RNA genome is 9,213 nucleotides long and encodes a polyprotein with 2,947 amino acids that is predicted to be cleaved into 10 mature proteins. The complete single open reading frame (ORF) of ArVY shares 47% and 34% nucleotide and amino acid sequence identity, respectively, with the closest related virus, soybean yellow shoot virus. Electron microscopic analysis revealed elongated viral particles typical of those found in plant cells infected with potyviruses.